Peak expiratory flow rate and its correlation with height among 6 to 14 years children: a cross sectional study - Gunasekaran, A. (International Journal of Contemporary Pediatrics, 2021)
Background: The objective of this research was to study the peak expiratory flow rate (PEFR) values and its correlation with height in children aged between 6 to 14 years and height. Methods: A cross sectional study was conducted among 1205 children aged 6 to 14 years in department of paediatrics at a medical college hospital. In a pre-structured questionnaire, the age, sex, height and PEFR values were recorded. PEFR was considered as primary outcome variable. SPSS version 20 was used for data analysis. Results: Among 1205 study participants, height showed a steady relationship with PEFR. As height increases PEFR increases progressively in both boys and girls. (R2=0.691). The linear regression model for PEFR with height of all age shows, one centimeter increase in height there was 5.1% increase in PEFR with a constant (-458.0) and a 95% confidence interval 4.9 to 5.3, a lesser R2=69.1% which was found to be statistically significant. Conclusions: The PEFR values derived and its height correlation in this study can be used as reference for children in and around Chennai district.